The acute neuromuscular responses to cluster set resistance training: A systematic review and meta-analysis - Latella, C.; Teo, W.-P.; Drinkwater, E. J.; Kendall, K.; Haff, G. G. (Sports Medicine, 2019)
Background: Cluster sets (CSs) are a popular resistance training (RT) strategy categorised by short rest periods implemented between single or groups of repetitions. However, evidence supporting the effectiveness of CSs on acute intra-session neuromuscular performance is still equivocal. Objective: The objective of this investigation was to determine the efficacy of a single session of CSs to attenuate losses in force, velocity and power compared to traditional set (TS) training. Methods: Screening consisted of a systematic search of EMBASE, Google Scholar, PubMed, Scopus and SPORTDiscus. Inclusion criteria were (1) measured one or more of mean/peak force, velocity or power; (2) implemented CSs in comparison to TSs; (3) an acute design, or part thereof; and (4) published in an English-language, peer-reviewed journal. Raw data (mean ± standard deviation) were extracted from included studies and converted into standardised mean differences (SMDs) and?±?95% confidence intervals (CIs). Results: Twenty-five studies were used to calculate SMD ± 95% CI. Peak (SMD = 0.815, 95% CI 0.105-1.524, p = 0.024) and mean (SMD = 0.863, 95% CI 0.319-1.406, p = 0.002) velocity, peak (SMD = 0.356, 95% CI 0.057-0.655, p = 0.019) and mean (SMD = 0.692, 95% CI 0.395-0.990, p < 0.001) power, and peak force (SMD = 0.306, 95% CI - 0.028 to 0.584, p = 0.031) favoured CS. Subgroup analyses demonstrated an overall effect for CS across loads (SMD = 0.702, 95% CI 0.548-0.856, p < 0.001), included exercises (SMD = 0.664, 95% CI 0.413-0.916, p < 0.001), experience levels (SMD = 0.790, 95% CI 0.500-1.080, p < 0.001) and CS structures (SMD = 0.731, 95% CI 0.567-0.894, p < 0.001) with no difference within subgroups. Conclusion: CSs are a useful strategy to attenuate the loss in velocity, power and peak force during RT and should be used to maintain neuromuscular performance, especially when kinetic outcomes are emphasised. However, it remains unclear if the benefits translate to improved performance across all RT exercises, between sexes and across the lifespan.